KOMUNIKASI ANTAR BUDAYA DALAM PENINGKATAN HUBUNGAN HARMONIS ANTAR KARYAWAN DI SEKOLAH PRIMEONE SCHOOL KOTA MEDAN - Butar Butar, Dewi Sartika; Piolina, Piolina; Dalimunthe, Syukur Kholil; Lubis, Zulkifli (LPPM Universitas Darma Agung, 2020)
This study aims at finding out the pattern of intercultural communication that occurs in a prime one school environment; the social and cultural values ​​in enhancing harmonious relations within the PrimeOne School Medan employees and the factors that support and hinder employees in communicating at school. This research was conducted at the private school PrimeOne School in Medan. The research informants were determined by purposive sampling and Snowball Sampling based on certain criteria. This type of research is a descriptive study using a qualitative approach. Primary data were obtained through direct observation and in-depth interviews with informants. Meanwhile, secondary data obtained from data collection through documents in the form of books, journals, the internet, and photos related to the research topic. The data collected was then analyzed using the Miles and Huberman Interactive Analysis Model. The results of this study indicate that initially cultural differences, especially language, became a challenge both for foreign students and local students in communicating so that cross-cultural communication patterns that occur between foreign employees and local employees as well as interactions with students in communicating at school are very tortuous and experience difficulty. But over time, the interaction of the two gradually improved. In addition, social needs as humans to interact and communicate become supporting factors that encourage both to always be involved in conversation.